Adverse outcome of AML with aberrant CD16 and CD56 NK cell marker expression. Issue 3 (3rd June 2018) - Junge, Alexandra; Bacher, Ulrike; Mueller, Beatrice U.; Keller, Peter; Solenthaler, Max; Pabst, Thomas
Abstract: Natural killer cells mediate antibody‐dependent cell‐mediated cytotoxicity, and CD16 exerts key functions to induce antibody‐dependent cell‐mediated cytotoxicity response. Because the prognostic relevance of aberrant CD16 expression in AML patients at diagnosis is unknown, we analyzed 325 AML patients undergoing intensive chemotherapy for aberrant CD16+ and CD56+ natural killer‐cell marker expression. CD56+ AML patients had inferior median event‐free (EFS; P  = 0.0699) and overall survival (OS; 10.9 versus 20.6 months; P  = 0.0132). Patients expressing CD16 had worse median EFS ( P  = 0.0622) and OS (13.0 versus 45.9 months; P  = 0.0277). EFS for CD16+/CD56+ patients was 5.7 months compared with 7.1 months for CD16−/CD56− ( P  = 0.3690), and OS was 10.6 months for CD16+/CD56+ patients compared with 52.2 months for CD16−/CD56− patients ( P  = 0.0311). Patients with CD16+/CD56+ expression had a lower probability to achieve complete remission after 2 induction cycles (52% versus 72%). Our data suggest that AML patients with aberrant CD16 and CD56 expression have adverse survival outcomes.